The effect of modeling strategy on inferential thinking and acquiring the performance attacking skills in handball - Ombarak, Mohammed (Humanities Journal of University of Zakho, 2020)
The aim of this study is to reveal the effect of the modeling strategy on inferential thinking and acquiring the art of performing attacking skills in handball, and the researcher used the experimental method and used the design with two groups of experimental and control groups with pre and post test for its suitability to the objectives of the research and its problem. The research community consisted of (52) students of the second stage in the Department of Physical Education / Faculty of Education / University of Zakho for the academic year 2019-2020. As for the research data collection tools, it included the inferential thinking scale (Mufti, 1997) which the researcher codified on the local environment and found the scientific basis for it. In addition to tests of art of performing attacking skills in the game of handball. The researcher used the SPSS statistical method to process the data and the researcher reached to the following conclusions. The modeling strategy and the traditional method contributed to the development of inductive thinking and raising the level of art of performing attacking skills in the handball game of the experimental and control groups. The experimental group that used the modeling strategy excelled the control group with positive results in developing inferential thinking and raising the level of the art of performing attacking skills in the game of handball. Keywords: (modeling strategy, inferential thinking, handball)